BUILDING COMMUNICATION ETHICS IN STUDENTS OF SMP MUHAMMADIYAH IN BANDA ACEH - Adli, Adli (Program Studi Sosiologi Universitas Malikussaleh, 2024)
Cultural changes in communication can be witnessed in people's habits, especially teen agers who are still at school, if in this era of conventional communication media, it is done to consider and maintain social ethical values and norms, to form a strong student behavior in student, they must b able to imitate the behavior of the Prophet Muhammad SAW who had perfect behavior. The formation of student morals is very oy important to implement in various the conditions, including the use of technology used by students at Muhammadiyah Middle School in Banda Aceh, which is an educational institution and educational institution that has a complex and dynamic system as a place for students to develop commendable behavior so that they yi can become a generation to be proud of. Based on explanation above, this discussion will focus on what forms of communication moral development for all Muhammadiyah Middle School students in Banda Aceh City are? Then the purpose of this research is to the understand the form of communication moral development for students at Muhammadiyah Middle School in Banda Aceh. The type of research used is a descriptive qualitative approach, namely field research. The results obtained by the author in thi research are that the form of communication moral development in students is carried out through a model or method that is in accordance with the behavior lovinec that educators exemplify to all their students, especially good communication works methods that are in accordance with the guidance of the Prophet Muhammad SAW.